THE USE OF PICTURES TO IMPROVE VOCABULARY MASTERY IN COMPREHENDING DESCRIPTIVE TEXT OF SECOND YEAR STUDENTS’ AT SMP TUAH NEGERI PEKANBARU - Abu Bakar Syabli; Erni '; Syarfi K ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This Classroom Action Reserach (CAR) to find the mastery of the second year students at SMP Tuah Negeri Pekanbaru in using picture. The aims at this research to increase vocabulary mastery using pictures in comprehending descriptive text of the second year students. This research was conducted in two cycles that consisted of four meeting in each cycle. This research was conducted to overcome the existing problem on the field as well as to described and to explain whether the pictures media could improve the students’ vocabulary mastery. The result of this research average score in pre-test is 49, average scores in cycle 1 is 67 and average scores in cycle 2 is 72. The result of this research indicated that the pictures media could improve the students’ vocabulary mastery. It was also found that; The selection of appropriated pictures media; The application of pictures; The management activities of the class & practiced; and teacher support can increase students motivation in vocabulary mastery in comprehending descriptive text.Key Words: Improve, Vocabulary Mastery,and Picture